Le partage inégal des « tâches ménagères » - Roland Pfefferkorn (Les Cahiers de Framespa)
During the last decades women were the actresses of the changes that affected the marital relations, and they reached a bigger autonomy regarding these relations. In contrast, the household space is still dominated by what we could call the domestic power. Thanks to the feminists, and their criticism of the domestic division of labour, we are now aware that domestic work is done mostly by women, and we know that this division of work is not natural. Domestic work includes a set of very varied activities, from the “domestic tasks” themselves – to which the present article will limit itself –, to the management of income or holdings of the family, the education of the children, the care of the dependent persons – in particular the old and\or disabled ones –, or the organization of the family space-time. The various surveys about the division of the tasks between men and women all show today the same disparities as those pointed out by the feminists one generation ago, even in the couples where both spouses work full-time.